2014
DOI: 10.1186/s13243-014-0006-z
|View full text |Cite
|
Sign up to set email alerts
|

Developing performance management systems for the green supply chain

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 47 publications
(109 reference statements)
0
25
0
1
Order By: Relevance
“…Yu, et al (2014) identified the relationship between green SCM and the dimensions of operational performance, and determined the measurements of SC performance. Mutingi, et al (2014) regard green SC as vital in improving the performance management system. Green SC is also a new comprehensive index that may be used to combine performance appraisal and analysis of environmental and economic performances.…”
Section: Research Methodology With the Hypotheses Investigatedmentioning
confidence: 99%
“…Yu, et al (2014) identified the relationship between green SCM and the dimensions of operational performance, and determined the measurements of SC performance. Mutingi, et al (2014) regard green SC as vital in improving the performance management system. Green SC is also a new comprehensive index that may be used to combine performance appraisal and analysis of environmental and economic performances.…”
Section: Research Methodology With the Hypotheses Investigatedmentioning
confidence: 99%
“…The authors discussed difficulty of finding KPIs with a wide applicability range across different sectors. Mutingi et al, (2014) developed a framework, named the taxonomic performance measurement framework, to measure sustainability performance within the context of SCM [302]. The proposed concept had a strong emphasis on the environmental aspect, but with less focus on the other two pillars.…”
Section: Past Lean-based Sustainability Assessment Frameworkmentioning
confidence: 99%
“…To execute such a green concept, organizations need to be aware of fundamental environmental concerns, such as emissions into the air, e.g., greenhouse gases (GHGs), ozone depletion, dust and particles, emissions into the water, e.g., wastewater or emissions into the soil, e.g., solid waste (Mutingi et al, 2014). Greenhouse gases, however, are the top environmental issue, a concern for both developed and developing countries, many of which have vowed to reduce their greenhouse gas emissions.…”
Section: Introductionmentioning
confidence: 99%